Subject–Verb Number Agreement in Bilingual Processing: (Lack of) Age of Acquisition and Proficiency Effects - Nuria Sagarra; Nicole Rodriguez (Languages, 2022)
Children acquire language more easily than adults, though it is controversial whether this faculty declines as a result of a critical period or something else. To address this question, we investigate the role of age of acquisition and proficiency on morphosyntactic processing in adult monolinguals and bilinguals. Spanish monolinguals and intermediate and advanced early and late bilinguals of Spanish read sentences with adjacent subject–verb number agreements and violations and chose one of four pictures. Eye-tracking data revealed that all groups were sensitive to the violations and attended more to more salient plural and preterit verbs than less obvious singular and present verbs, regardless of AoA and proficiency level. We conclude that the processing of adjacent SV agreement depends on perceptual salience and language use, rather than AoA or proficiency. These findings support usage-based theories of language acquisition.